PERBANDINGAN PEMBERIAN BRODIFAKUM LD50 DAN LD100 TERHADAP PERUBAHAN GAMBARAN HISTOPATOLOGI USUS HALUS TIKUS WISTAR - Alfian Salahudin Al Ayoubi; Tuntas Dhanardhono; Sigit Kirana Lintang Bhima (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background : Brodifacoum is an anticoagulant substance which usually used as pest control, but this substance has a poisoning effect the body. Brodifacoum is absorbed through gastrointestinal tract which can cause the disorder of blod clotting by slowing down the process of epoxide reductase of vitamin-K.Aim : To know the comparison of Histopathology Rattus norvegicus Intestine against brodifacoum administration LD50 and LD100.Methods :This study was an experimental study with post test only group design. The sample of this study are 27 Rattus norvegicus which given per oral administration of brodifacoum. Barthel Manja scores were used to assess changes in intestine Histopatology. Normal and desquamation are a minor damage, while erosion and ulcers are major damage. Non-parametric test of Mann-Whitney to the results are revealed significant if p <0.05.Results :On LD50, 2 rats died on days 3, 5 on day 5, and 2 rats terminated on day 7. In LD100 2 rats died on day 3, 2 on day 5, and 5 rats terminated on day 7. On LD50 groups there are 66,67% minor damage and 33,33% major damage, while in LD100 groups there are 55,56% minor damage and 44,44% major damage. Test non parametric Mann-Whitney in the control group with LD50 was found p = 0.269, in control group with LD100 was found p = 0106, then group with the LD50 and LD100 found p = 0.159.Conclusion :There are not significant differentiation of histopatology picture between LD50 and LD100 dose ( p = 0.159 )